2022
DOI: 10.1158/1538-7445.am2022-3022
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3022: Tryptophan metabolism is associated with obesity and triple negative breast cancer risk in black and white women

Abstract: Non-Hispanic black (NHB) women are more likely to be diagnosed and die from triple negative breast cancer (TNBC) than non-Hispanic white (NHW) women. We previously showed that TNBC tissues display a distinct microbial signature. Obesity which contributes to chronic low-grade inflammation and gut microbial dysbiosis further exacerbates TNBC outcomes for NHB women. However, it is unclear the extent to which microbial differences in breast tumor tissues may be driven by alterations in microbial metabolites as a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Random forest analysis showed a unique biochemical signature associated with elevated L-Tryptophan and Kynurenine metabolites and lower levels of microbial-derived metabolites critical for controlling inflammation and immune response in obese individuals and those with TNBC. Additionally, analysis of The Cancer Genome Atlas revealed that the expression of key Lenzymes was significantly associated with worse survival outcomes in TNBC patients (Smith et al, 2022). Overall, these findings suggest a complex interplay between bacterial metabolism, tryptophan derivatives, obesity, and breast cancer development and progression.…”
Section: Microbial-derived Metabolites As Signaling Moleculesmentioning
confidence: 85%
See 1 more Smart Citation
“…Random forest analysis showed a unique biochemical signature associated with elevated L-Tryptophan and Kynurenine metabolites and lower levels of microbial-derived metabolites critical for controlling inflammation and immune response in obese individuals and those with TNBC. Additionally, analysis of The Cancer Genome Atlas revealed that the expression of key Lenzymes was significantly associated with worse survival outcomes in TNBC patients (Smith et al, 2022). Overall, these findings suggest a complex interplay between bacterial metabolism, tryptophan derivatives, obesity, and breast cancer development and progression.…”
Section: Microbial-derived Metabolites As Signaling Moleculesmentioning
confidence: 85%
“…Tryptophan metabolism has also been associated with obesity and TNBC. (Smith A, et al, 2022) investigated alterations in microbial metabolism pathways in breast tissues of obese women relative to non-obese women with and without TNBC. Random forest analysis showed a unique biochemical signature associated with elevated L-Tryptophan and Kynurenine metabolites and lower levels of microbial-derived metabolites critical for controlling inflammation and immune response in obese individuals and those with TNBC.…”
Section: Microbial-derived Metabolites As Signaling Moleculesmentioning
confidence: 99%